2015
DOI: 10.2169/internalmedicine.54.0668
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adiponectin Levels and Changes in Glucose Metabolism before and after Treatment for Thyroid Dysfunction

Abstract: Objective Adiponectin is an adipokine which is known to decrease in individuals associated with obesity and insulin resistance. In this study, we aimed to investigate the serum adiponectin levels and glucose metabolism in patients with thyroid dysfunction before and after treatment. Methods Newly diagnosed overt hypothyroid (n=20) and thyrotoxic (n=23) patients and healthy controls (n=20) with a body mass index of <30 kg/m 2 were evaluated prospectively. Patients with a known state of insulin resistance, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
(65 reference statements)
2
8
0
2
Order By: Relevance
“…In fact, a positive association between fasting plasmatic insulin or HOMA-IR index and TSH levels has been described in some cross-sectional studies, 16,24,25,59,66,70,82,84,94,100 which was confirmed in a cohort analysis of 5998 subjects. 34 However, the increase in serum TSH levels may be an effect of weight gain based on several previously described mechanisms.…”
Section: Studies Evaluating the Association Between Metabolic Syndrommentioning
confidence: 59%
“…In fact, a positive association between fasting plasmatic insulin or HOMA-IR index and TSH levels has been described in some cross-sectional studies, 16,24,25,59,66,70,82,84,94,100 which was confirmed in a cohort analysis of 5998 subjects. 34 However, the increase in serum TSH levels may be an effect of weight gain based on several previously described mechanisms.…”
Section: Studies Evaluating the Association Between Metabolic Syndrommentioning
confidence: 59%
“…Therefore, serum adiponectin maybe altered by other therapeutic measures, such as improving metabolic syndrome by medicine [31], and weight loss [32]. Furthermore, Ozdemir et al showed that a significant decrease in the adiponectin levels was observed after treatment for hypothyoidism [33]. However, only CPAP intervention was assessed in our meta-analysis, and the results of several studies in the meta-analysis suggested that CPAP treatment did improve hypoxemia and sleep fragmentation, but had little impact on BMI and insulin resistance in OSA patients, (details were shown in Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Temuan ini konsisten dengan temuan Ozdemir, dkk. 16 dan Litaka, dkk. 17 yang menyatakan intoleransi glukosa pada pasien hipertiroid akan membaik dengan perbaikan status klinis tiroid.…”
Section: Hubungan Status Klinis Tiroid Dengan Intoleransi Glukosaunclassified